SHEAR AND CREEPING STRENGTH OF OPTIMUM MIXES (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
In this article the results of laboratory tests of samples of two optimum mixes to shear and creeping strength are presented. In an optimum mix the clay components are presented by swelling bentonite clays of Sarigukh deposit and Miocene reddish clays of Erebuni. As additive compound in optimum mixes dust of volcanic tuff and slag was used. It is established, that in optimum mixes the presence of volcanic tuff and slag leads to cohesion decrease and internal friction increase.
Keywords: bentonite clays; shear and creeping strength; volcanic tuff; Miocene reddish clays